Investigating colostomy-related morbidity in children following stoma formation and closure in a tertiary hospital, Abha, Saudi Arabia: a retrospective cohort study 2024 - Hashim Ali Alghamdi; Meshari Saad M Alqahtani; Hatem Mostafa Mohammed Asiri; Abdulaziz Mohammed M Abudasir; Khalid Talab Salem Alshahrani; Rahaf Ahmed Alamer; Ali Abdullah S Alshahrani; Yasir Abduallah M Alyahya; Anas Mohammed abudasir; Saeed Jarallah S AlQahtani; Ghassan E. Mustafa Ahmed (BMC, 2024)
Abstract Background Overall, stoma-related morbidity affects a reported 20-38% of pediatric patients. However, determining the true incidence of major stoma-related morbidity is challenging due to limited cohort sizes in existing studies. Thus, the aim of this study was to investigate colostomy related morbidity among children both after stoma formation and stoma closure. Methodology This is a retrospective cohort hospital-based study, conducted in an Abha maternity and children hospital, between August 1, 2018, and August 1, 2023, among 126 pediatric patients (aged 0-12 years) who underwent colostomy formation and subsequent closure during the study period. Data were collected from medical records. Data was analyzed using Statistical Package for Social Sciences (SPSS) v.26. Results This study included a total of 126 children who underwent colostomy. (N = 37, 29.4%) of cases included in this study were emergency cases, while (N = 89, 70.6%) were elective. A variety of antibiotics were used for surgical prophylaxis, metronidazole (77%) and cefuroxime (62.7%) were the most prevalent. Oral feeding was started after 5-6 days in more than one third of cases (39.7%). Wound infection (N = 15, 11.9%) was the most reported post-operative complication, followed with bowel obstruction (N = 6, 4.8%). Emergency cases had a longer duration of hospital stay than elective cases; this difference was statistically significant (P = .04). Conclusions Majority of patients reported no stoma related complications, while among those who reported complications, wound infection was the most reported complication, followed by bowel obstruction.